2022
DOI: 10.1097/qad.0000000000003403
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of frailty among adults living with HIV aged 70 years or older

Abstract: Objectives and design:Frailty is a phenotype associated with adverse health outcomes in older persons. It has been evaluated mainly in middle-aged persons with HIV (PWH). The French multicenter prospective ANRS EP66 SEPTAVIH study aimed to assess frailty prevalence and risk factors in PWH aged 70 years or older on antiretroviral treatment (ART) for at least 12 months.Methods:At baseline, Fried frailty phenotype criteria, sociodemographic data, medical/HIV history, functional status, comorbidities, including im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…Similar to previous studies [13, 43, 44], we found that parameters linked to CD4 cells were not associated with frailty. This was not surprising, as the study population consisted of individuals on regular ART, with undetectable viral load and no active opportunistic disease.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to previous studies [13, 43, 44], we found that parameters linked to CD4 cells were not associated with frailty. This was not surprising, as the study population consisted of individuals on regular ART, with undetectable viral load and no active opportunistic disease.…”
Section: Discussionsupporting
confidence: 91%
“…Nearly all participants assessed in the present study had virological control, and their levels of T CD4 + were high. Our cohort is representative of older PWH under efficient antiretroviral therapy in France, as assessed in the original baseline results of the SEPTAVIH study [16]. As such, our results can probably apply to PWH aged more than 70 years with efficient virological control.…”
Section: Discussionmentioning
confidence: 97%
“…Participants in this study were those included in the ANRS EP66 SEPTAVIH cohort. The ANRS EP66 SEPTAVIH cohort is a French, multicentre, prospective observational study assessing the prevalence and incidence of frailty and prefrailty in PWH aged 70 years or older as well as their predictors (Clinicaltrials.gov NCT03958786) [16]. PWH aged 70 years or older had to be on antiretroviral therapy (ART) for more than 12 months.…”
Section: Populationmentioning
confidence: 99%
“…An alternative approach, is the comprehensive geriatric assessment (CGA) and frailty based approach pioneered in Brighton, UK (the Silver Clinic) [42]. Frailty is increasingly recognized in individuals ageing with HIV and reported to be highly prevalent in both high income [43] and African studies [44], though one Tanzanian study reported low prevalence in a cohort with access to high quality medical care [45].…”
Section: Interventional Approachesmentioning
confidence: 99%